2010
DOI: 10.1130/g31034.1
|View full text |Cite
|
Sign up to set email alerts
|

Two large meteorite impacts at the Cretaceous-Paleogene boundary

Abstract: The end-Cretaceous mass extinction has been attributed by most to a single asteroid impact at Chicxulub on the Yucatán Peninsula, Mexico. The discovery of a second smaller crater with a similar age at Boltysh in the Ukraine has raised the possibility that a shower of asteroids or comets impacted Earth close to the Cretaceous-Paleogene (K-Pg) boundary. Here we present palynological and δ 13 C evidence from crater-fi ll sediments in the Boltysh impact crater. Our analyses demonstrate that a post-impact fl ora, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 33 publications
(36 reference statements)
1
46
0
Order By: Relevance
“…Whether pre-boundary environmental perturbations (either global or regional) had a progressive effect on the reduction of biotic diversity is debatable (Jolley et al, 2010). Declining taxonomic diversity is apparent throughout the Maastrichtian in many taxonomic groups (e.g.…”
Section: Summary and Broader Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether pre-boundary environmental perturbations (either global or regional) had a progressive effect on the reduction of biotic diversity is debatable (Jolley et al, 2010). Declining taxonomic diversity is apparent throughout the Maastrichtian in many taxonomic groups (e.g.…”
Section: Summary and Broader Implicationsmentioning
confidence: 99%
“…These contrasting views are likely to reflect idiosyncrasies common to interpreting data from the fossil record (Keller and Abramovich, 2009) and more subtle effects exerted by preconceived conclusions (Valen, 1984). Identifying a single cause for the K-T extinction has therefore been challenging, and a multicausal scenario remains a viable alternative (Birkelund and Håkansson, 1982;Keller et al, 2003;Archibald and Fastovsky, 2004;Jolley et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although originally ascribed to an asteroid impact, iridium and energy constraints yield a best estimate that the impactor was a comet 10-80 km in diameter (Durand-Manterola & Codero-Tercero 2014). However a detailed stratigraphic study of the Ukrainian Boltysh crater by Jolley et al (2010) has shown that it was formed only 2000-2500 years before the Chicxulub impact in the Gulf of Mexico (the radiometric age given in Table1 has standard deviation ±0.6 Myr). This short timescale is consistent with the breakup of a large short-period comet yielding N Earthcrossing fragments with dynamical or physical lifetimes L yr such that N L > ∼ C, where C represents the mean lifetime of a fragment before collision with the Earth.…”
Section: Bombardment Intensities and Causesmentioning
confidence: 99%
“…It is thus not possible to use radioisotope dating to prove beyond doubt that two impacts were simultaneous. In fact, recent research on sediments from the Boltysh Crater shows that it formed as little as 2000 years before Chicxulub (Jolley et al, 2010). The conclusion is derived from an estimate based upon the flora in sediments recovered from a drill core of the crater fill which indicate that the local area of the ejecta blanket became colonized by earlysequence plants after the impact, but that this ecosystem was in turn suddenly devastated by a second event, believed to be the result of the Chicxulub impact.…”
Section: Other Dating Techniquesmentioning
confidence: 96%